2016
DOI: 10.1177/0143034316666413
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the high school classroom environment on learning as mediated by student engagement

Abstract: Classroom learning environments are frequently assumed to exert their influence on learning indirectly, via student engagement. The present study examined the influence of environmental challenge and support on learning in high school classrooms, and the potential for student engagement to act as a mediator in this relationship. Data were collected in seven classrooms in six different subjects in several US high schools. The 104 students in these classes participated in the Experience Sampling Method (ESM) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 49 publications
2
60
0
9
Order By: Relevance
“…The revised literature recognizes certain design factors involved in the classroom and their level of impact, both on the motivation [2,43,49,50] and on the social relations of the students [28,38,45]. The impact factors of the university classroom on managing of socio-educational well-being are grouped into three dimensions: physical-environmental, socio-perceptual and motivational.…”
Section: Impact Factors Of the University Classroom On Socio-educatiomentioning
confidence: 99%
See 2 more Smart Citations
“…The revised literature recognizes certain design factors involved in the classroom and their level of impact, both on the motivation [2,43,49,50] and on the social relations of the students [28,38,45]. The impact factors of the university classroom on managing of socio-educational well-being are grouped into three dimensions: physical-environmental, socio-perceptual and motivational.…”
Section: Impact Factors Of the University Classroom On Socio-educatiomentioning
confidence: 99%
“…The physical-environmental dimension establishes the relationship between the physical factors or conditions of the environment and its influence on the development of learning processes. From a holistic perspective, a series of variables The design, quality and adequacy of learning spaces encourage students to maintain positive emotions, feel integrated and, thereby, to experience more favorable academic results [28,49,52,53]. Academic achievement is influenced by the articulation between the physical and architectural conditions of the building, and the social and perceptual environment that students appreciate from them, impacting their performance and motivation [50].…”
Section: Impact Factors Of the University Classroom On Socio-educatiomentioning
confidence: 99%
See 1 more Smart Citation
“…Lawson (2017) categorised engagement research into three main approaches: statebased, process-based and trait-based/identity-laden The state based research focuses on how the learner responds to learning in context, concerned with creating a responsive environment that facilitates learning through effective relationships within a classroom situation (e.g. (Shernoff, Ruzek, & Sinha, 2017). The process-based approach is rooted in theories of motivation and that re-engagement processes that appeal to learner motivations is key in understanding engagement (e.g.…”
Section: Engagementmentioning
confidence: 99%
“…The internet and wireless technology promote interlink amidst mobile gadgets with other computing devices such as computers, tablets, and other items (Hinostroza et al, 2016). Recently empirical research has revealed the benefits of using wireless technology and portable gadgets in high school learning surrounding to enhance accessibility and convenience of information interconnection (Shernoff et al, 2017). Helping students to participate in learning-related activities regardless of where they are, offering support to groups working on a plan, and improving communication and joint education in the classroom is essential.…”
Section: Technology and Student Collaboration And Motivationmentioning
confidence: 99%